26- HISTOMORPHOLOGY OF HAEMOLYMPH NODES OF WATER DEER (HYDROPOTES INERMIS ARGYROPUS): NOVEL STUDY - Artemeva E.A (Basrah Journal of Veterinary Research)
The objective of the present work was to investigate the anatomical and histological structures of haemolymph nodes in the adult water deer (Hydropotes inermis argyropus). Methodology: the morphology of haemolymph nodes from 5 adult water deer was studied by gross inspection and by histological methods. Results: the haemolymph nodes were determined for the first time in water deer (Hydropotes inermis argyropus). The nodes located in the neck on the trachea, thoracic and abdominal cavities in water deer. Dark red in color and oval- or round shaped haemolymph nodes in water deer were observed particularly along the abdominal aorta and caudal vena cava; as well as on the trachea along the jugular vein, on the internal carotid artery and internal jugular vein and on the aortic arch. These nodes had a hilus with hilar vessels, which entered the haemolymph nodes through the trabeculae as trabecular artery. The parenchyma was organized in the form of cortex and medulla. Lymphoid rim was located between subcapsular sinus and cortex. The cortex was composed of a many secondary lymphoid follicles and diffuses interfollicular lymphoid tissue, and medulla contained medullary cords and medullary sinuses. A reticular meshwork extended throughout the haemolymph nodes formed the structure backbone. The interstices of the reticular meshwork were filled with free blood cells, many macrophages, lymphocytes, and plasma cells. Conclusion: the dark red haemolymph nodes of water deer examined were seen along the course of large blood vessels in the neck on the trachea, thoracic and abdominal cavities. This is first study has demonstrated the presence of haemolymph nodes in water deer (Hydropotes inermis argyropus) and provided essential information on their anatomical and histological structures. The data obtained in the present study may be used for further research in this field